Silencing the porcine iGb3s gene does not affect Galα3Gal levels or measures of anticipated pig‐to‐human and pig‐to‐primate acute rejection. (11th January 2016) - Butler, James R.; Skill, Nicholas J.; Priestman, David L.; Platt, Frances M.; Li, Ping; Estrada, Jose L.; Martens, Gregory R.; Ladowski, Joseph M.; Tector, Matthew; Tector, A. Joseph
Abstract: Background: The Galα(1, 3)Gal epitope (α‐GAL), created by α‐ 1, 3‐glycosyltransferase‐1 (GGTA1), is a major xenoantigen causing hyperacute rejection in pig‐to‐primate and pig‐to‐human xenotransplantation. In response, GGTA1 gene‐deleted pigs have been generated. However, it is unclear whether there is a residual small amount of α ‐Gal epitope expressed in GGTA1 −/− pigs. Isoglobotrihexosylceramide synthase (iGb3s), another member of the glycosyltransferase family, catalyzes the synthesis of isoglobo‐series glycosphingolipids with an α‐GAL‐terminal disaccharide (iGb3), creating the possibility that iGb3s may be a source of α‐GAL epitopes in GGTA1 −/− animals. The objective of this study was to examine the impact of silencing the iGb3s gene (A3GalT2) on pig‐to‐primate and pig‐to‐human immune cross‐reactivity by creating and comparing GGTA1 −/− pigs to GGTA1 −/− ‐ and A3GalT2 −/− ‐double‐knockout pigs. Methods: We used the CRISPR/Cas 9 system to target the GGTA1 and A3GalT2 genes in pigs. Both GGTA1 and A3GalT2 genes are functionally inactive in humans and baboons. CRISPR‐treated cells used directly for somatic cell nuclear transfer produced single‐ and double‐gene‐knockout piglets in a single pregnancy. Once grown to maturity, the glycosphingolipid profile (including iGb3) was assayed in renal tissue by normal‐phase liquid chromatography. In addition, peripheral blood mononuclear cells (PBMCs) were subjected to (i) comparative cross‐match cytotoxicity analysis against human and baboon serum and (ii) IB4 staining for α‐GAL/iGb3. Results: Silencing of the iGb3s gene significantly modulated the renal glycosphingolipid profile and iGb3 was not detected. Moreover, the human and baboon serum PBMC cytotoxicity and α‐GAL/iGb3 staining were unchanged by iGb3s silencing. Conclusions: Our data suggest that iGb3s is not a contributor to antibody‐mediated rejection in pig‐to‐primate or pig‐to‐human xenotransplantation. Although iGb3s gene silencing significantly changed the renal glycosphingolipid profile, the effect on Gal α 3Gal levels, antibody binding, and cytotoxic profiles of baboon and human sera on porcine PBMCs was neutral.